2022
DOI: 10.1186/s12877-022-03672-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends and influence factors in the prevalence, intervention, and control of metabolic syndrome among US adults, 1999–2018

Abstract: Aim We aimed to describe the trends in the prevalence, intervention, and control of metabolic syndrome (MetS) among US adults through 1999–2018. Additionally, the influence factors of MetS and its control were further explored. Methods We included participants older than 20 using the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 (n = 22,114). The rate of prevalence, intervention, and control of MetS were caculated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…A meta-analysis of the association of age distribution with MetS prevalence in the general population of Bangladesh found that a 1-year increase in age was associated with a 4% increase in MetS prevalence in the general population of the characteristic age group [32]. Similarly, in national epidemiological surveys in China [25] and the United States [33], we have found that the prevalence or risk of MetS is signi cantly higher in the age group above 45 years. When looking speci cally at the population of drug naïve schizophrenia patients, we also found that the group of patients with comorbid MetS was older[28], and that the prevalence of MetS was signi cantly higher in patients with adult onset than in those with early onset [29].…”
Section: Discussionsupporting
confidence: 54%
“…A meta-analysis of the association of age distribution with MetS prevalence in the general population of Bangladesh found that a 1-year increase in age was associated with a 4% increase in MetS prevalence in the general population of the characteristic age group [32]. Similarly, in national epidemiological surveys in China [25] and the United States [33], we have found that the prevalence or risk of MetS is signi cantly higher in the age group above 45 years. When looking speci cally at the population of drug naïve schizophrenia patients, we also found that the group of patients with comorbid MetS was older[28], and that the prevalence of MetS was signi cantly higher in patients with adult onset than in those with early onset [29].…”
Section: Discussionsupporting
confidence: 54%
“…According to data from the National Health Survey (PNS), the prevalence of MS among Brazilians is 38.4%, being higher in women, individuals with low education and the elderly [3]. This overall prevalence is similar to the results of the National Health and Nutrition Examination Survey 2 (NHANES) 2011-2016, in which MS affected 34.7% of the US population [4]. Research carried out in the city of Vitória, capital of the state where the municipality of the present study is located, found that 29.8% of individuals had MS according to the National Cholesterol Education Program's Adult Treatment Panel III NCEP/ATP III criteria, with no difference in sex, but with an increase to 48.3% in the age group from 55-64 years-old [5].…”
Section: Introductionmentioning
confidence: 53%
“…The association of at least three of the following pathological conditions defines MetS: elevated waist circumference (≥88 cm in women and ≥102 cm in men), elevated triglycerides (≥150 mg/dL), reduced high-density lipoprotein cholesterol (HDL-C) (<40 mg/dL in men and <50 mg/dL in women), elevated blood pressure (≥130 mmHg systolic blood pressure or ≥85 mmHg diastolic pressure or drug treatment for arterial hypertension), and elevated fasting glucose (≥100 mg/dL or drug treatment for elevated glucose) [81]. The prevalence of MetS has increased over the years, both in the general adult population [82] and in specific subpopulations, such as patients undergoing LT [83]. Approximately half of the patients undergoing LT develop MetS within 3 years post LT [83], and the mortality rate in post-LT patients with MetS is four times higher than in those without MetS [84].…”
Section: Metabolic Syndromementioning
confidence: 99%